Plant parasitic nematodes associated with the cultivation quinoa in the Puno region, Perú - Lima-Medina, Israel (2019)
Phytoparasites such as nematodes attack without showing signs of symptoms, while they can prevent the passage of nutrients and the normal growth of the plant. In the region of Puno, the genus Globodera spp. is the most important pest, however there are no reports for Meloidogyne spp. Thus, the objective of this research is to identify the different genera of phytoparasite nematodes in the cultivation of quinoa in the main production areas of the Puno region. Soil samples were collected in the provinces of Puno, Huancané, San Román, Chucuito, Collao, Yunguyo and Azángaro. Nematode extraction from soil samples was carried out by the centrifugal fluctuation method with sucrose and mounted on permanent sheets for morphological studies.The genera of phytoparasite nematodes identified were Meloidogyne spp., Nacobbus spp., Pratylenchus spp., Helicotylenchus spp., Mesocriconema spp., Xiphinema spp., Dorylaimus spp., Hemiciclyophora spp., Globodera spp. and free-living nematodes. It should be noted that the genus with the highest presence in quinoa in all samples was Globodera spp.